Biomarkers associated with rheumatoid arthritis and their relationship with venous thromboembolism - Velásquez-Cano, Juan Pablo (2023)
Introduction: Rheumatoid arthritis is a chronic autoimmune disease primarily characterized by progressive joint damage and extra-articular manifestations. Objective: To analyze the importance of corresponding biomarkers for rheumatoid arthritis and how they contribute to the diagnosis of venous thromboembolism. Materials and methods: An advanced search was conducted in PubMed, Embase (Elsevier), Google Scholar, and Scopus, yielding 69 articles. Results: Different biomarkers were identified, and those allowing the analysis of how rheumatoid arthritis leads individuals with the disease to develop venous thromboembolism were described, such as D-dimer, C-reactive protein, lncRNAs, and ACPAs. Conclusion: Rheumatoid arthritis is an autoimmune disease that may lead individuals to develop venous thromboembolism, which can be confirmed through the described biomarkers.